Prevalence, Socio-demographic Factors and Psychosocial Work Hazards of Primary School Teachers: A School-based Cross-sectional Study - Okeke, Chinedu Ifedi; Ede, Moses Onyemaechi; Maba, Aprezo Pardodi (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2022)
This study investigated the prevalence, socio-demographic factors, and psychosocial work hazards of primary school teachers. This is a cross-sectional study that recruited 254 primary school teachers. The responses from the participants were collected using Copenhagen psychosocial questionnaire and teachers’ socio-demographic questionnaire. Bar chart, mean, standard deviation, and bivariate analysis were used to analyze the data collected. The result showed a high level of work-related psychosocial hazard among primary school teachers. The results showed that teachers’ age has a positive relationship with psychosocial work hazards. Also, the result showed that working status and years of experience have a significant relationship with psychosocial work hazards. Therefore, occupational health experts should consistently conduct psychosocial risks assessments on the teachers.